CASH WAQF PRACTICES IN MALAYSIA AND INDONESIA - Hardianti Yusuf; Muspita Sari (Jurnal Al-Dustur, 2022)
This paper is a study of the practice of Waqf-Al-Nuqud in Malaysia and Indonesia. How is the practice of cash waqf in each of these countries by looking at the results and allocations. This problem is described by comparative research, namely research conducted to compare a variable (object of research), between different subjects and find a causal relationship. The research is directed to find out whether between two or more groups there are differences in the aspects or variables studied. Based on the results of the discussion, the author understands that the waqf practice carried out by Malaysia and Indonesia can be seen the difference. The practice of cash waqf in Malaysia is better known as stock waqf where cash waqf is collected from various circles of society with a stock waqf system by setting a minimum number of share prices that can be purchased by the public which will later be used as a property waqf that is utilized according to the purpose of waqf according to sharia. As for Indonesia, the practice of classical waqf is still very widespread. Regulations have been adequate even with the rules for managing it, but it seems that not many people know about cash waqf which is easier and more affordable. However, the presence of TWI has become a breath of fresh air for the development and socialization of cash waqf in Indonesia. TWI also issued a cash waqf certificate as a form of eternal cash waqf. It can be seen that TWI is still the community's choice for waqf compared to BWI which is a national waqf institution. But in reality, according to TWI regulations, it is not the institution intended to issue cash waqf certificates.